Chemical investigation of semi purified shorea robusta gum resin by using GCMS - D.Vishakante Gowda; Krishan Manral; Babu UV; Sarathchandraprakash; Jampala Balaji; Dr.K.Suresh Babu; S.Anubala (International Journal of Pharmacy and Analytical Research, 2015)
The chemical investigation was done on Semi purified Shorea robusta gum resin (SG) to identify the chemical moieties. N-hexane fraction Shorea robusta gum, fractions were done by using column chromatography. The fractionation done by changing the polarities of n-Hexane and chloroform. All the fractions were collected carefully and solvents were removed by using Buchi Rotavapor. The collected fractions were subjected for GCMS evaluation. This study reveals the probable chemical components which were presenting in each and every fractions based on mass spectrums of GCMS. In the semi fractions of gum resin of Shorea robusta, the 100% hexane fraction was shown good emulsifying property. Based on the GCMS data, the probability of the molecular formulas of the components in 100% hexane fraction were C9H12, C13H28, C14H30, C10H22, C11H24, C12H26, C8H18, C9H19I, C8H16O, C6H14, C15H18O2, C9H14O2, C15H24, C16H34, C17H36, C14H30O3S, C14H31BO, C15H26O. This study gave the information about the probability of molecular formulas and its molecular structures of the components present in the semi fractions of gum resin of Shorea robusta based on GCMS data.